Transventricular Left Bundle Branch Pacing - Perepeka, Eugene O.; Kravchuk, Borys B.; Paratsii, Oksana M.; Hrubyak, Liliana M.; Leonchuk, Volodymyr L.; Sychyk, Maryna M. (Ukrainian Journal of Cardiovascular Surgery, 2022)
Background. Implementation of conduction system permanent pacing methods in patients with cardiac bradyarrhythmias allows to maintain the physiological sequence of excitation and contraction of the ventricles and to avoid the development of heart failure due to electrical and mechanical dyssynchrony in patients with high rates of ventricular pacing. Case description. A 61-year-old female patient was examined and treated at the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine from January 25 to January 27, 2022 at the department of surgical treatment of complex cardiac arrhythmias with a diagnosis of proximal complete atrioventricular block. A two-chamber pacemaker (Vitatron Q50A2) with a ventricular lead to stimulate the His bundle region (Medtronic 3830, 69 cm) was implanted to the patient with a special delivery system (C315HIS). At an X-ray operating room, 12 ECG leads from the electrophysiological station LabSystem Pro (Bard, USA) were connected to the patient to analyze the criteria for capturing the conduction system on stimulation during ventricular lead placement, and a diagnostic quadripolar electrode was inserted into the right ventricle to record the potential of the His bundle as an X-ray reference point. During placement of the ventricular lead in the area of the His bundle due to high pacing thresholds the decision was made to implement an alternative method of conduction system pacing – left bundle branch pacing through the interventricular septum. After gradual passage of the electrode through the septum, capture of the conduction system of the heart was achieved, although no clear potential of the left bundle was registered. The interval from stimulus to peak R wave in lead V6 was 68 ms, and the interval from stimulus to peak R wave in lead V1 was 110 ms. The difference between intervals was 42 ms, which indicated the criteria of nonselective capture of the left bundle branch, with stimulation thresholds below 1 V at a pulse length of 0.5 ms. In the postoperative period, the patient was evaluated for global longitudinal deformity of the left ventricle on constant ventricular stimulation, which was carried out according to standard methods using speckle-tracking echocardiography; no signs of dyssynchrony were found. Also, the location of the endocardial electrode in the middle segments of the interventricular septum on the right ventricular side was visualized and confirmed by performing B-mode transthoracic echocardiography with subcostal access. Conclusions. Left bundle branch pacing, like His bundle pacing, maintains electrical and mechanical synchrony of the left ventricle at lower pacing thresholds, greater amplitude of the sensitivity signal and lower risks of lead dislocation.